Answer: ![\dfrac{x^2+1}{2}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%5E2%2B1%7D%7B2%7D)
Step-by-step explanation:
Given
![f(x)=\sqrt{2x-1}](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%7B2x-1%7D)
We can write it as
![\Rightarrow y=\sqrt{2x-1}](https://tex.z-dn.net/?f=%5CRightarrow%20y%3D%5Csqrt%7B2x-1%7D)
Express x in terms of y
![\Rightarrow y^2=2x-1\\\\\Rightarrow x=\dfrac{y^2+1}{2}](https://tex.z-dn.net/?f=%5CRightarrow%20y%5E2%3D2x-1%5C%5C%5C%5C%5CRightarrow%20x%3D%5Cdfrac%7By%5E2%2B1%7D%7B2%7D)
Replace y be x to get the inverse
![\Rightarrow f^{-1}(x)=\dfrac{x^2+1}{2}](https://tex.z-dn.net/?f=%5CRightarrow%20f%5E%7B-1%7D%28x%29%3D%5Cdfrac%7Bx%5E2%2B1%7D%7B2%7D)
To prove, it is inverse of f(x). ![f(f^{-1}(x))=x](https://tex.z-dn.net/?f=f%28f%5E%7B-1%7D%28x%29%29%3Dx)
![\Rightarrow f(f^{-1}(x))=\sqrt{2\times \dfrac{x^2+1}{2}-1}\\\\\Rightarrow f(f^{-1}(x))=\sqrt{x^2+1-1}\\\\\Rightarrow f(f^{-1}(x))=x](https://tex.z-dn.net/?f=%5CRightarrow%20f%28f%5E%7B-1%7D%28x%29%29%3D%5Csqrt%7B2%5Ctimes%20%5Cdfrac%7Bx%5E2%2B1%7D%7B2%7D-1%7D%5C%5C%5C%5C%5CRightarrow%20f%28f%5E%7B-1%7D%28x%29%29%3D%5Csqrt%7Bx%5E2%2B1-1%7D%5C%5C%5C%5C%5CRightarrow%20f%28f%5E%7B-1%7D%28x%29%29%3Dx)
So, they are inverse of each other.
I simplified this equation and received.
Answer: 550
Elaborate what you want to solve of this is not what was wanted.
Answer:
30% students
Step-by-step explanation:
Let x be the number of total students of a school.
63% are girls then total number of girls = (0.63)x
37% are boys then total number of boys = ( 0.37)x
Now 23% of girls wear contacts then total number of girls
= (0.63x) × 0.23
= (0.1449x)
And 42% of boys wear contacts then total number of boys wearing contacts
= (0.37x) ( 0.42)
= (0.1554)x
Total students wears contacts = ( 0.1449x) + (0.1554x)
= (0.3003x)
Percentage of students wear contacts =
× 100
=
× 100
= 30%
All 30% students wear contacts.
5.95 is your answer. Have a wonderful day
Step-by-step explanation:
L = length
W = width
L = W + 9
A = 112 = LW = (W+9)W
So,
W2 + 9W = 112
W2 + 9W - 112 = 0
Factoring
(W-7)(W+16) = 0
W = 7, -16
We discard W = -16, since a measurement cannot be negative.
W = 7
And since L = W + 9, then L = 7 + 9 = 16
This is a 16x7 rectangle